2019
DOI: 10.1038/s41598-019-39546-y
|View full text |Cite
|
Sign up to set email alerts
|

Goat and buffalo milk fat globule membranes exhibit better effects at inducing apoptosis and reduction the viability of HT-29 cells

Abstract: Bovine milk fat globule membrane (MFGM) has shown many health benefits, however, there has not been much study on non-cattle MFGMs. The purpose of this study was to compare the anti-proliferation effects and investigate the mechanisms of MFGMs from bovine, goat, buffalo, yak and camel milk in HT-29 cells. Results showed that protein content in MFGM of yak milk is the highest among five MFGM. All MFGMs reduced cellular viability which was in agreement with cell morphology and apoptosis. However, the number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…While researchers are still making efforts to understand the functionalities of MFGM, there are already commercialized products supplementing MFGMs from bovine milk cream. The effectiveness of supplementation of MFGM in formula has been demonstrated in several independent cellular and animal studies, and clinical trials [25][26][27][28]. In Bovine milk based infant formulas have attempted to closely mimic the lipid composition of naturally originated breast milk.…”
Section: Breast Milk Fat Globulesmentioning
confidence: 99%
“…While researchers are still making efforts to understand the functionalities of MFGM, there are already commercialized products supplementing MFGMs from bovine milk cream. The effectiveness of supplementation of MFGM in formula has been demonstrated in several independent cellular and animal studies, and clinical trials [25][26][27][28]. In Bovine milk based infant formulas have attempted to closely mimic the lipid composition of naturally originated breast milk.…”
Section: Breast Milk Fat Globulesmentioning
confidence: 99%
“…Among all the tested samples, buffalo and goat MFGMs were more effective in inducing apoptosis than the other three MFGMs. These data suggest that MFGM might be a putative agent for the prevention of human colon cancer [16].…”
Section: Comparison Of Mfgm Proteome Between Different Species and Lamentioning
confidence: 69%
“…An example of the application of these comparative studies was given recently by Ji and collaborators [16], who evaluated the antiproliferative effect of five MFGM fractions from yak, bovine, goat, camel, and buffalo milk using the HT-29 cell line. The antiproliferative effect was evaluated in terms of cell viability, cell cycle, cytomorphology, apoptosis, and mitochondrial membrane potential (MMP).…”
Section: Comparison Of Mfgm Proteome Between Different Species and Lamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, MFGM is capable of inducing apoptosis in human colon cancer cells (HT-29) via the reduction of cell proliferation and increasing the caspase-3 activity, which known as one of the programmed cell death marker, cell cycle arrest in S phase, increasing the apoptotic protein Bax, downregulating the anti-apoptotic protein Bcl-2, and decreasing mitochondrial membrane potential. The data suggested that some of the MFGMs could be used as potential agents for human colon cancer prevention [45,46].…”
Section: Discussionmentioning
confidence: 99%